THE ECONOMIC IMPACT OF NATIVE CHICKEN FARMING (NON-BREED) ON FAMILY INCOME (Study in Sojomerto Village, Reban District, Batang Regency) - Rokh Eddy Prabowo; Bambang Sutejo; Agus Murdiyanto (Faculty of Economic and Business Universitas STIKUBANK, 2023)
In rural areas, there are fewer and fewer native chicken (non-breed or free-range) businesses run by household units. In other words, even though other households no longer raise free-range chickens, there are still households that do. When they have free-range chickens, they have the potential to earn more money than many other households. Furthermore, according to febroni (kompas.com), the native chicken livestock business has become one of the most promising in recent years. Year after year, the demand for chicken meat grows because there are more and more restaurants and street stalls selling native chicken menus. This statement is backed up by https://bukukas.co.id, which claims that